2018
DOI: 10.1111/josh.12587
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Social Contexts of Physical Activity Behaviors of Fifth and Seventh Grade Youth

Abstract: Boys and girls reported declines in the variety and frequency of activities from fifth to seventh grade. There were sex-specific patterns in physical activities and groups; however, all participants reported home as the primary location and a shift to class/team groups over time. Schools are well-positioned to provide additional physical activity opportunities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 51 publications
1
21
2
Order By: Relevance
“…Adolescents, particularly boys, are less likely to participate in PA outside of team/peer settings. 10 , 11 , 12 , 28 , 29 The current study demonstrated that PA with friends decreased for outdoor activity, suggesting families were actively abiding by social distancing mandates and restricting peer interactions.…”
Section: Discussionmentioning
confidence: 55%
“…Adolescents, particularly boys, are less likely to participate in PA outside of team/peer settings. 10 , 11 , 12 , 28 , 29 The current study demonstrated that PA with friends decreased for outdoor activity, suggesting families were actively abiding by social distancing mandates and restricting peer interactions.…”
Section: Discussionmentioning
confidence: 55%
“…One reason for this was that younger children increased outdoor independent play, while high school-aged adolescents did not ( Tulchin-Francis et al, 2021 ). Adolescents may be less likely to participate in physical activity outside of team and peer settings, particularly boys ( Saunders et al, 2018 , Tulchin-Francis et al, 2021 ). In one study, about half (52%) of U.S. adolescents reported no longer being physically active after California’s stay-at-home orders ( Chaffee et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…They mainly stated that, for a more effective public health policy, the public should be ensured to participate in physical activities. Kobau et al [35] and Saunders et al [36] also determined that, as a result of physical activities, some diseases will decrease, and this will contribute to the improvement of public health.…”
Section: Literature Reviewmentioning
confidence: 99%